CORROSION PROCESSES IN BRAKE FRICTION PAIRS - Vudvud, Oleksandr (Problems of Friction and Wear, 2025)
The article discusses theoretical studies of corrosion processes in brake friction pairs in closed and open states used in lifting and transport equipment. Electrochemical corrosion is a heterogeneous and multistage process caused by the thermodynamic instability of the working surfaces of friction pairs in a given corrosive environment. The main calculation parameters of corrosion processes in friction pairs of brake devices are: local area of action; maximum permissible speed; permissible depth of influence; wear of micro-protrusion contact spots per unit of time; loss of micro-protrusion mass. It has been established that the sources of contact corrosion are: energy levels of materials (triboelectric effect), air and water, and the formation of electrolyte on the working surface of the lining during the destruction of its materials. The metal-polymer friction pair is a cathode (-) and an anode (+). The process of electrochemical corrosion is a combination of two related reactions: anodic (oxidation) and cathodic (reduction) , where Ox is a depolarizer (oxidizer) that attaches n electrons released as a result of the anodic reaction (metal ionization), Red is the reduced form of the oxidizer. A schematic diagram of the electrochemical destruction of the working surface of the overlay is presented. At the anodic sites (+), atoms lose and the ions formed pass into the solution , while the released electrons move from the anodic sites to the cathodic sites (-). Oxidizing agent (depolarizer) molecules Ox approach the cathode areas from the solution and attach themselves, forming the reduced form of the oxidizing agent - Red. It turns out that electrochemical corrosion on a heterogeneous surface of the overlay is similar to the operation of a short-circuited galvanic cell. The following features of the electrochemical corrosion process have been identified, which can be represented as two simultaneously occurring but largely independent electrode processes: anodic (ionization of the overlay) and cathodic. The kinetics of the anodic and cathodic processes, and therefore the corrosion rate, depend on the electrode potential of the metal; the electrode processes are localized in different areas of the working surface of the lining, where their flow is facilitated; material losses can be established mainly in the anodic areas of the lining surface.